Ensuring the Effectiveness of Education through Interactive Methods in the Modern Pedagogical Process - Rashid, Tokhtamurodova Laylo; Khurshid, Rakhmatullayeva Lobar (ASEAN Journal of Educational Research and Technology, 2025)
This study explores the effectiveness of interactive teaching methods in enhancing student learning outcomes and classroom engagement. Specifically, it focuses on the use of strategies such as “Cluster,” “Brain Ring,” “Mind Wheel,” “Insert,” and “Role Playing” in a higher education setting. A quasi-experimental design was implemented involving 80 second-year students at a university in Tashkent, divided into control and experimental groups. While the control group received instruction through traditional lecture-based methods, the experimental group was taught using the aforementioned interactive techniques. Data were collected through assessments measuring knowledge retention, participation, creativity, critical thinking, and teamwork. The results showed that the experimental group outperformed the control group across all indicators. Among the methods applied, the “Cluster” technique stood out as particularly effective in stimulating idea organization, promoting active learning, and fostering group collaboration. These findings support the integration of interactive pedagogical strategies as a means to improve the quality and effectiveness of education. Ultimately, such methods contribute to the development of future-ready learners equipped with essential 21st-century skills.